Impact Of Organizational Culture And Job Satisfaction On Nurse Performance In General Hospital : A Path Analysis - Giovanni Iga Firmanda; Ahsan Ahsan; Retno Lestari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The performance of health employees influences hospital quality service standards. Nurses play an essential role in developing and monitoring the quality of healthcare services through organizational culture, job satisfaction, and work motivation. This study aimed to investigate the impact of organizational culture and job satisfaction on nurse performance using work motivation as a moderating variable. This study takes a cross-sectional approach with a quantitative design. The research sample included 131 people who were chosen at random (proportionate stratified random sampling). Questionnaires were used to collect data, and its validity and reliability were tested. Data analysis is done via path analysis. The findings revealed that organizational culture impacted work motivation p=0.000 (p less than 0.05) and job satisfaction. The results showed that there was an influence of organizational culture on work motivation p=0.000 (p less than 0.05), job satisfaction on work motivation p=0.000 (p less than 0.05), organizational culture did not affect performance p=0.629 (p more than 0.05), job satisfaction on performance p= 0.000 (p less than 0.05), work motivation on performance p = 0.000 (p less than 0.05). This demonstrates that work motivation is crucial in boosting nurse performance through organizational culture and job satisfaction. A supportive organizational culture promotes nurses' performance in terms of patient safety and quality. In conclusion, a positive work environment promotes contented nurses, which affects health care quality.